1981
DOI: 10.1007/bf00239116
|View full text |Cite
|
Sign up to set email alerts
|

The structure of bimodal chemo-, thermo-, and hygroreceptive sensilla on the antenna of Locusta migratoria

Abstract: Coeloconic sensilla on the antenna of Locusta migratoria were investigated electrophysiologically, labeled and then examined under the scanning or transmission electron microscope. They can be categorized into two main morphological types: 1) sensilla with wall pores and two concentric cuticular walls (wp-dw sensilla), and 2) sensilla lacking wall pores (np-sensilla). Hygroreceptors were observed only in np-sensilla. Olfactory receptors were observed in wp-dw sensilla, but not in np-sensilla. Cold-sensitive un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
77
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(89 citation statements)
references
References 5 publications
5
77
0
Order By: Relevance
“…The coeloconic sensillum described in this study similar to that observed in L. migratoria (Altner et al, 1981) and the basiconic sensillum of P. americana are reported to possess stimulus-conducting pores similar to those of olfactory sensilla (Steinbrecht, 1969;Altner et al, 1973, 1977and Yokohari et al, 1975.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…The coeloconic sensillum described in this study similar to that observed in L. migratoria (Altner et al, 1981) and the basiconic sensillum of P. americana are reported to possess stimulus-conducting pores similar to those of olfactory sensilla (Steinbrecht, 1969;Altner et al, 1973, 1977and Yokohari et al, 1975.…”
Section: Discussionsupporting
confidence: 71%
“…This is explained as hygroreceptors of honey bees were shown to respond to a deformation of the sensillum, similar to that shown for cockroach hygroreceptors (Yokohari, 1978). Sensilla of similar structure have been identified as hygro-and thermoreceptors (Altner et al, 1978;Tichy, 1979 andAltner et al, 1981). Thermoreceptors of the cockroach are found in both the capitular sensillum (Yokohari et al, 1975) and in the grooved sensillum (Altner et al, 1977 andYokohari, 1983).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations